PENGARUH E-SERVICE QUALITY DAN E-TRUST TERHADAP KEPUTUSAN PENGGUNAAN PINJAMAN ONLINE EASYCASH - Lina, Lina; Tyra, Maria Josephine (Forum Bisnis Kewirausahaan, 2025)
This study aims to determine the effect of E-Service Quality and E-Trust on the decision to use. The data used in this study is primary data. The population in this research consists of users of online loan services on the EasyCash platform. The sampling technique applied was purposive sampling, involving a total of 100 respondents. Hypothesis testing was conducted using descriptive statistical analysis, data quality testing, classical assumption testing, as well as T-test and F-test, with results processed using SPSS. The findings of this study indicate that E-Service Quality and E-Trust implemented by EasyCash have a positive and significant effect on the decision to use online loans on the EasyCash platform. Kata Kunci: E-Service Quality, E-Trust, Decision to Use